2014
DOI: 10.5194/sed-6-1191-2014
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sedimentological characteristics of ice-wedge polygon terrain in Adventdalen (Svalbard). Environmental and climatic implications for the Late Holocene

Abstract: Abstract. Ice-wedges are widespread periglacial features in the landscape of Adventalen, Svalbard. The networks of ice-wedges have created areas with well-developed polygonal terrains in the lowest fluvial terraces in this valley. We have examined the sedimentological characteristics of the northern and southern banks of the Advent river for palaeoenvironmental purposes. The base of two sedimentary sections reported radiocarbon dates of 3.3 and 3.9 ka cal BP, respectively. The northern site is constituted by t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 68 publications
0
8
0
1
Order By: Relevance
“…4), which corresponds with the onset of ice-wedge formation in Adventdalen (Jeppesen 2001). Further to the east of site L2, up to 3.6 ka BP old peat within loess deposits is reported (Jeppesen 2001), Oliva et al (2014) even found up to 3.9 ka BP old peat in a loess exposure near site A2a. This indicates that the maximum age of loess accumulation increases upvalley.…”
Section: Holocene Landscape Changesmentioning
confidence: 99%
See 1 more Smart Citation
“…4), which corresponds with the onset of ice-wedge formation in Adventdalen (Jeppesen 2001). Further to the east of site L2, up to 3.6 ka BP old peat within loess deposits is reported (Jeppesen 2001), Oliva et al (2014) even found up to 3.9 ka BP old peat in a loess exposure near site A2a. This indicates that the maximum age of loess accumulation increases upvalley.…”
Section: Holocene Landscape Changesmentioning
confidence: 99%
“…[Colour figure can be viewed at www.boreas.dk] tal trends such as palaeo-wind, -snow and -moisture regime, as considered in e.g. Oliva et al (2014).…”
Section: Holocene Landscape Changesmentioning
confidence: 99%
“…C) yielded an age of ca 2·9 ka as a minimum age for permafrost there (Jeppesen, ). Dating results from two other sites in that area have indicated that the aeolian deposits of FA VII began to accumulate between 3·3 ka and 3·9 ka (Oliva et al ., ). Cable et al .…”
Section: Discussionmentioning
confidence: 97%
“…The syngenetic assemblage of cryofacies CF2, CF6, CF8 and CF9 (Table ) formed in the deposits of FA VII, where the upward growth of permafrost followed the accumulation of aeolian sediment (Bryant, ; Oliva et al ., ). These cryofacies developed as segregated ice at the top of permafrost (Cheng, ; Mackay, ), as observed also in terraces at the flanks of Adventdalen and other valleys in central Spitsbergen (Vtyurin, ; Härtel, ).…”
Section: Discussionmentioning
confidence: 97%
“…A diferencia del Ártico donde son abundantes (ej. : FORTIER y ALLARD, 2004;Oliva et al, 2014), estas geoformas no están tan profusamente representadas en los enclaves libres de hielo de la Antártida RAFFI y STENNI, 2011;LÓPEZ-MARTÍNEZ et al, 2012). Los suelos ordenados adquieren mayor desarrollo en los ambientes húmedos de las playas levantadas altas que en las bajas.…”
Section: V1c Deglaciación De La Península Byers Y Generalización Dunclassified